2023
DOI: 10.3389/fimmu.2023.1114006
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation produced by senescent osteocytes mediates age-related bone loss

Abstract: PurposeThe molecular mechanisms of age-related bone loss are unclear and without valid drugs yet. The aims of this study were to explore the molecular changes that occur in bone tissue during age-related bone loss, to further clarify the changes in function, and to predict potential therapeutic drugs.MethodsWe collected bone tissues from children, middle-aged individuals, and elderly people for protein sequencing and compared the three groups of proteins pairwise, and the differentially expressed proteins (DEP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…[25][26][27] In addition to exosome release, senescent osteocytes may also function in other ways, such as producing inflammation or SASP. 14,27 These possibilities were not explored in our study. Instead of isolating primary cells from aged mice, we induced senescence in MLO-Y4 cells through application of oxidative stress for our experiments.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…[25][26][27] In addition to exosome release, senescent osteocytes may also function in other ways, such as producing inflammation or SASP. 14,27 These possibilities were not explored in our study. Instead of isolating primary cells from aged mice, we induced senescence in MLO-Y4 cells through application of oxidative stress for our experiments.…”
Section: Discussionmentioning
confidence: 95%
“…11 Osteoblast function weakens with ageing, and limited bone formation or mineralization cannot fill the resorption cavity left by osteoclasts, resulting in bone mass loss and bone microarchitecture disorder. This process is known to be influenced by several factors, including the cellular microenvironment, hormone levels, inflammation, vascularization, oxidative stress, etc, [12][13][14][15] but the major regulators have yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of osteocytes in postmenopausal osteoporosis still needs to be clarified. Recent studies have shown that damage to the function of osteocytes can lead to a variety of bone diseases, [ 17 , 18 , 78 ] but the changes experienced by osteocytes in postmenopausal osteoporosis patients have not been determined. In this study, we determined that osteocytes in postmenopausal osteoporosis experienced ferroptosis and that ferroptotic osteocytes affected the process of bone loss by regulating osteoclast‐mediated bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…We found that these DETh17RGs are mainly enriched in Cellular senescence, Wnt signaling pathway, and Hippo signaling pathway. The study found that the senescence-associated secretory phenotype (SASP) produced by cell aging accumulates in the bone microenvironment, thereby further inducing bone aging [24]. The Wnt signaling pathway is a key signaling pathway for the osteogenic differentiation of MSCs, and the Wnt signaling pathway can activate β-catenin to regulate gene transcription, thereby promoting osteoblast proliferation and differentiation [25].…”
Section: Discussionmentioning
confidence: 99%